PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PRODUKSI CV TIRTA MAKMUR UNGARAN - Ilma Kurnia Isnani; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2018)
Human resources play a major role to run the life of the organization. Various factors can affect the performance of employees, including intra-role and extra-role behaviors. Extra-role behavior or better known as Organizational Citizenship Behavior (OCB) and self efficacy are important factors for better employee performance. The purpose of this study is to find out the influence of Organizational Citizenship Behavior (OCB) and self efficacy on the performance of CV Tirta Makmur Ungaran production employees. The type of research used is explanatory research, with a total sample of 67 respondents using a saturated sampling approach. Collecting data using a questionnaire with Likert measurement scale. Data analysis methods used are validity and reliability, simple linear regression test, multiple linear regression test, correlation coefficient, determination coefficient, and significance test (t test and F test) with SPSS For Windows 21.0. The results of this study indicate that the variables Organizational Citizenship Behavior (OCB) and self efficacy have a significant and positive influence on employee performance, both partially and simultaneously. Partially OCB has an effect of 31% on employee performance. Self efficacy has a significant (partial) effect on employee performance by 25.5%. While together OCB and self efficacy have a significant influence of 37.1% on employee performance. Based on the results of research on the magnitude of the effect of OCB and self efficacy, it is recommended that companies pay more attention to the extra behavior of production employees of CV Tirta Makmur Ungaran and increase employee confidence to work better every day.